Alternative transfer to the Earth-Moon Lagrangian points L4 and L5 using lunar gravity assist - Salazar, F. J. T.; Macau, E. E. N.; Winter, O. C. [UNESP] (Elsevier B.V., 2014)
Lagrangian points L4 and L5 lie at 60 degrees ahead of and behind the Moon in its orbit with respect to the Earth. Each one of them is a third point of an equilateral triangle with the base of the line defined by those two bodies. These Lagrangian points are stable for the Earth Moon mass ratio. As so, these Lagrangian points represent remarkable positions to host astronomical observatories or space stations. However, this same distance characteristic may be a challenge for periodic servicing mission. This paper studies elliptic trajectories from an Earth circular parking orbit to reach the Moon's sphere of influence and apply a swing-by maneuver in order to re-direct the path of a spacecraft to a vicinity of the Lagrangian points L4 and L5. Once the geocentric transfer orbit and the initial impulsive thrust have been determined, the goal is to establish the angle at which the geocentric trajectory crosses the lunar sphere of influence in such a way that when the spacecraft leaves the Moon's gravitational field, its trajectory and velocity with respect to the Earth change in order to the spacecraft arrives at L4 and L5. In this work, the planar Circular Restricted Three Body Problem approximation is used and in order to avoid solving a two boundary problem, the patched-conic approximation is considered. (C) 2013 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Stable Lagrangian points; L4; L5; Three Body Problem; Patched-conic; Swing-by